THE EFFECT OF ZUMBA GYMNAST TO THE IMPROVEMENT OF CARDIOVASCULAR HEAT RESPONSES IN SCHIZOPHRENIA CLIENTS IN RSJ PROVINSI BALI - Ni Komang Sukra Andini; Desak Made Ari Dwi Jayanti (Stikes Wira Medika Bali, 2017)
The Cardiovascular endurance is the ability of the heart, lungs and blood vessels inproviding oxygen for muscle therefore the muscles can contract. The purpose of this studywas to knew the effect of zumba gymnast in improving the cardiovascular endurance on clients with schizophrenia in the RSJ Bali Province.The research design of this study was used a quasi experimental designwithout group control. The sample used by 10 people and given training in the form of Zumba gymnastics, for six weeks, in a given period three times with duration 45 minutes.The results showed that the mean of cardiovascular endurance pre-test 31,80 ± 3,15 ml / kg / min, post-test 33,90 ± 4,48 ml / kg / min (p <0,05) with paired analysis Sample test there was an increase in mean cardiovascular endurance of 2.1 ml / kg / min. The conclusion that there was a zumba gym effect on cardiovascular endurance in patients with schizophrenia in RSJ Bali Province. It can be suggested to the RSJ Bali Province to give zumba gym training regularly and continuously